LEARNING STYLES OF AUSTRALIAN TEACHERS IN LEARNING BAHASA INDONESIA (BIPA) AT UIN MAULANA MALIK IBRAHIM MALANG - Djoko Susanto (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2015)
This research examines the learning styles (Fleming, 1987) – visual, auditory, and kinesthetic (VAK) of Aus-tralian teachers in learning bahasa Indonesia (BIPA) at UIN Maulana Malik Ibrahim Malang. This research was undertaken to answer the following questions: (1) what kinds of learning styles performed by the Australian teachers in learning bahasa Indonesia at UIN Maulana Malik Ibrahim Malang? and (2) what kinds of categories of each learning style mostly reflected by the Australian teachers in learning bahasa Indonesia at UIN Maulana Malik Ibrahim Malang? The data were collected by doing short survey, classroom observations, questionnaires, and interviews with both students and teachers (Robson, 2002). The results of the study shows that (1) more participants were kinesthetic learners. Most of them learnt bahasa Indonesia best through a hand – on method, exploring the world around them, and often relying on what they could directly experience or perform; (2) Its categories mostly suited with the participants’ learning style: more time for outside learning, as the participants needed to know more about the language and practice it within its cultural context. Most of them enjoyed very much tasks which involve manipulating materials and objects. Finally, they also liked learning bahasa Indonesia through moving, doing, and touching.